EVALUASI KEBIJAKAN DANA BANTUAN PENYELENGGARAAN PENDIDIKAN KABUPATEN LAMPUNG BARAT - Yesi Merinda; Riswanti Rini; Sowiyah Sowiyah (Program Studi Magister Manajemen Pendidikan)
The purpose of this study is to provide a descriptive evaluation of the implementation of education aid policy in West Lampung. The method used is descriptive approach to evaluation by interview, observation and documentation. Informants consisted of BAPPEDA, Dept. of Education, principals, treasurer BPP, teachers, students and community leaders.The results of this study indicate that Evaluation of the context of this policy have a clear basis since the beginning is based on the fact of the education, Evaluation of input local authorities have had the readiness of the budget and long-term analyzes are both related to the implementation of this policy, participation in this policy; Evaluation process of channeling funds have been well understood by all parties and did not leave ambiguity of meaning the distribution, implementation of school can be run according to the rules set forth, and in case there are problems yet significant constraints and; Evaluation monitoring products performed well, teachers and students feel motivated, and provide long-term effect on increasing the APK. Tujuan penelitian ini untuk memberikan evaluasi deskriftif mengenai kebijakan dana bantuan penyelenggaraan pendidikan di Kabupaten Lampung Barat. Metode yang digunakan adalah pendekatan evaluasi deskriftif model cipp dengan teknik wawancara, observasi, dan dokumentasi,informan terdiri dari BAPPEDA,Kepala Dinas Pendidikan, kepala sekolah, bendahara BPP, guru, siswa, dan elemen masyarakat. Hasil penelitian menunjukkan bahwa evaluasi konteks kebijakan ini memiliki dasar yang jelas sejak awal penyusunannya, Evaluasi input hasil menunjukkan bahwa pihak pemerintah daerah telah memiliki kesiapan anggaran dan analisis jangka panjang yang baik terkait dengan pelaksanaan kebijakan ini, kesiapan SDM sekolah sebagai objek pelaksana kebijakan ini juga telah siap dan tidak terdapat penolakan dari para personil sekolah baik pendidikanKata kunci : evaluasi, kebijakan dana BPP, model CIPP